Semi-detachable battery for non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2020093739
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-28
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-05-28
AI Technical Summary
【0009】 本発明の一態様によれば、シャットダウン温度、機械強度およびイオン透過性が両立できている非水電解液二次電池用セパレータが提供される。
Smart Images

Figure 0007645051000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator for a non-aqueous electrolyte secondary battery. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, have a high energy density and are therefore widely used as batteries for personal computers, mobile phones, portable information terminals, etc., and recently they have been developed as batteries for use in vehicles.
[0003] Polyolefin porous films are widely used as separators for non-aqueous electrolyte secondary batteries. Examples of properties required for such polyolefin porous films include a low shutdown temperature, high mechanical strength, and high ion permeability.
[0004] In this regard, Patent Document 1 discloses that (i) the weight average molecular weight is 5×10 5 Patent Document 2 discloses a microporous polyethylene membrane for separators, which comprises 70 to 99% by weight of the above polyethylene or a polyethylene composition thereof, and (ii) 1 to 30% by weight of a low-molecular-weight polyethylene having a weight-average molecular weight of 1000 to 4000 and a melting point of 80 to 130° C. Patent Document 2 discloses a microporous polyethylene membrane for separators, which comprises (i) a low-molecular-weight polyethylene having a weight-average molecular weight of 5×10 5 The present invention discloses a polyethylene microporous membrane comprising a polyethylene composition containing 20 to 98% by weight of the above polyethylene or a polyethylene composition thereof, and (ii) 2 to 80% by weight of a substantially linear ethylene-α-olefin copolymer produced using a single-site catalyst having a melting point of 95 to 125°C. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-259858 [Patent Document 2] Japanese Patent Application Publication No. 11-269289 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned conventional techniques have room for improvement in terms of compatibility between the shutdown temperature and mechanical strength and ion permeability. The microporous membrane disclosed in Patent Document 1 has a thickness of 25 μm and a Gurley value of at least 605 s / 100 mL. The polyethylene microporous membrane disclosed in Patent Document 2 has a thickness of 25 μm and a pin puncture strength of only 585 gf at most.
[0007] An object of one aspect of the present invention is to provide a separator for a non-aqueous electrolyte secondary battery that is capable of simultaneously achieving a good shutdown temperature, mechanical strength, and ion permeability. [Means for solving the problem]
[0008] The present invention includes the following configurations. <1> A separator for a non-aqueous electrolyte secondary battery containing a polyolefin resin as a main component, A separator for a non-aqueous electrolyte secondary battery, which has a maximum heat generation amount of 30 mW / g or more during isothermal crystallization at 128°C. <2> It contains polyethylene resin as its main component. <1> 2. The separator for a non-aqueous electrolyte secondary battery according to claim 1 . <3> <1> or <2> A laminate separator for a non-aqueous electrolyte secondary battery, comprising the separator for a non-aqueous electrolyte secondary battery according to claim 1, and a porous layer laminated on one or both sides of the separator for a non-aqueous electrolyte secondary battery, The porous layer of the laminate separator for a non-aqueous electrolyte secondary battery contains one or more resins selected from the group consisting of (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyimide resins, polyamideimide resins, polyester resins, and water-soluble polymers. <4> The porous layer contains an aramid resin. <3> 2. The laminate separator for a non-aqueous electrolyte secondary battery according to claim 1 . <5> A positive electrode and <1> or <2> A separator for a non-aqueous electrolyte secondary battery according to claim 1, <3> or <4> The laminate separator for a nonaqueous electrolyte secondary battery according to claim 1, A negative electrode; are arranged in this order. <6> <1> or <2> The separator for a non-aqueous electrolyte secondary battery according to claim 1, <3> or <4> The laminate separator for a non-aqueous electrolyte secondary battery according to claim 1, <5> A non-aqueous electrolyte secondary battery comprising the member for a non-aqueous electrolyte secondary battery according to claim 1. Effect of the Invention
[0009] According to one aspect of the present invention, there is provided a separator for a non-aqueous electrolyte secondary battery that is capable of simultaneously achieving a good shutdown temperature, mechanical strength, and ion permeability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each of the configurations described below, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments obtained by appropriately combining the technical means disclosed in different embodiments. In this specification, unless otherwise specified, "A to B" representing a numerical range means "A or more, B or less."
[0011] [1. Separator for non-aqueous electrolyte secondary batteries] A separator for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention contains a polyolefin resin as a main component, and has a maximum heat generation amount of 30 mW / g or more during isothermal crystallization at 128° C. The present inventors have found that a separator for a non-aqueous electrolyte secondary battery having a high parameter, "maximum heat generation amount during isothermal crystallization at 128° C.," is able to achieve a good balance between shutdown temperature, mechanical strength, and ion permeability.
[0012] In this specification, the "maximum heat generation amount during isothermal crystallization at 128°C" is measured by carrying out differential scanning calorimetry in the following order. Specifically, in the DSC curve obtained in step 4, the height (mW / g) of the maximum peak of heat generation accompanying crystallization is the "maximum heat generation amount during isothermal crystallization at 128°C." Step 1: Heat from 30℃ to 180℃ (10℃ / min) Step 2: Hold at 180℃ (5 minutes) Step 3: Decrease temperature from 180℃ to 128℃ (10℃ / min) Step 4: Hold at 128°C (480 minutes).
[0013] It is unclear how the maximum heat generation during isothermal crystallization at 128°C is specifically related to the properties of separators for non-aqueous electrolyte secondary batteries. Although it is hypothetical, it is believed that the primary structure of polyolefin molecules has a large effect on the DSC curve obtained by isothermal crystallization at 128°C.
[0014] That is, when polyolefin resin (particularly polyethylene resin) used as a raw material for separators for nonaqueous electrolyte secondary batteries is crystallized under rapid cooling conditions (about 10°C / min), the crystallization temperature is about 115±5°C. Therefore, crystallization under isothermal conditions at 128°C, which is slightly higher than this crystallization temperature, will cause the crystallization to proceed slowly. Therefore, it is considered that the influence of the primary structure (molecular weight, branching degree, etc.) of the polyolefin resin is more evident in the DSC curve obtained by isothermal crystallization at 128°C. In contrast, in normal differential scanning calorimetry, crystallization is performed under rapid cooling conditions (about 10°C / min). Therefore, it is considered that the influence of the primary structure of the polyolefin resin is not very evident in the obtained DSC curve.
[0015] The maximum heat generation amount during isothermal crystallization at 128° C. of the separator for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention is 30 mW / g or more, more preferably 40 mW / g or more, even more preferably 45 mW / g or more, and still more preferably 50 mW / g or more.
[0016] When the separator for a non-aqueous electrolyte secondary battery is subjected to differential scanning calorimetry, a predetermined weight of the separator for a non-aqueous electrolyte secondary battery is cut out and placed in an aluminum pan for measurement. When the separator for a non-aqueous electrolyte secondary battery is a laminate separator for a non-aqueous electrolyte secondary battery having a porous layer, the porous layer is peeled off before being subjected to differential scanning calorimetry. As a method for peeling off the porous layer, a method of attaching a peeling tape to the surface of the laminate separator for a non-aqueous electrolyte secondary battery on which the porous layer is formed and then peeling it off to peel off the porous layer as well can be mentioned. Alternatively, when the porous layer is water-soluble, the porous layer may be peeled off from the laminate separator for a non-aqueous electrolyte secondary battery by washing with water.
[0017] The melting point of the separator for non-aqueous electrolyte secondary batteries according to one embodiment of the present invention is preferably 136±7°C, more preferably 138±5°C. If the melting point is in the above range, it is considered that the characteristics of the primary structure of the polyolefin resin are sufficiently shown in the DSC curve when isothermal crystallized at 128°C. The heat of fusion of the separator for non-aqueous electrolyte secondary batteries according to one embodiment of the present invention is preferably 180 J / g or more, more preferably 210 J / g or more. If the heat of fusion is in the above range, it can be said that the polyolefin resin has a sufficient degree of crystallization, and therefore the parameters related to isothermal crystallization can be calculated with sufficiently high accuracy.
[0018] [Polyolefin resin] In this specification, "mainly composed of polyolefin resin" means that the proportion of polyolefin resin in the total material constituting the separator for nonaqueous electrolyte secondary batteries is 50% by volume or more, preferably 90% by volume or more, and more preferably 95% by volume or more.
[0019] The polyolefin resin, which is the main component of the separator for non-aqueous electrolyte secondary batteries, is not particularly limited. Examples of units constituting the polyolefin resin include units derived from olefin monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and 1-hexene. The polyolefin resin may be composed of units derived from only one type of olefin monomer, or may be composed of units derived from two or more types of olefin monomers. Examples of polyolefin resins that are homopolymers include polyethylene, polypropylene, and polybutene. Examples of polyolefin resins that are copolymers include ethylene-propylene copolymers. The separator for non-aqueous electrolyte secondary batteries may include only one type of the polyolefin resins described above, or may include two or more types.
[0020] In one embodiment, the separator for non-aqueous electrolyte secondary batteries contains an ethylene-based resin as a main component. In this specification, "containing a polyethylene-based resin as a main component" means that the proportion of the polyethylene-based resin in the total material constituting the separator for non-aqueous electrolyte secondary batteries is 50% by volume or more. This proportion is preferably 90% by volume or more, and more preferably 95% by volume or more. Separators for non-aqueous electrolyte secondary batteries containing a polyethylene-based resin as a main component tend to have a low shutdown temperature.
[0021] Examples of polyethylene resins include low-density polyethylene, high-density polyethylene, ultra-high molecular weight polyethylene, and linear polyethylene (ethylene-α-olefin copolymer).
[0022] In order to control the maximum heat generation amount during isothermal crystallization at 128°C, for example, the molecular weight of the polyolefin resin or the branching degree of the polyolefin resin may be adjusted. When a low molecular weight polyolefin resin is blended, the maximum heat generation amount tends to be high. Also, when the branching degree of the polyolefin resin is reduced, the maximum heat generation amount tends to be high.
[0023] In one embodiment, the polyolefin resin is a mixture of an ultra-high molecular weight component and a low molecular weight component. The upper limit of the weight average molecular weight of the ultra-high molecular weight component is preferably 6 million or less, more preferably 5.5 million or less, and even more preferably 5 million or less. The lower limit of the weight average molecular weight of the ultra-high molecular weight component is preferably 1.5 million or more, more preferably 1.8 million or more, and even more preferably 2 million or more. By setting the weight average molecular weight of the ultra-high molecular weight component in the above range, it is possible to achieve both the puncture strength and processability of the separator for non-aqueous electrolyte secondary batteries.
[0024] The upper limit of the weight average molecular weight of the low molecular weight component is preferably 10,000 or less. The lower limit of the weight average molecular weight of the low molecular weight component is preferably 1,500 or more, more preferably 2,000 or more. By setting the weight average molecular weight of the low molecular weight component within the above range, the dispersibility in the ultra-high molecular weight component is improved. In addition, the melting point of the low molecular weight component is preferably 115°C or more, more preferably 120°C or more, and even more preferably 125°C or more. By setting the melting point of the low molecular weight component within the above range, the maximum calorific value of the obtained polyolefin resin can be increased.
[0025] The blending ratio of the ultra-high molecular weight component to the low molecular weight component is preferably from (95:5) to (50:50), more preferably from (90:10) to (55:45), and even more preferably from (85:15) to (60:40). In one embodiment, the total content of the ultra-high molecular weight component and the low molecular weight component in the entire polyolefin resin is preferably 70% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more.
[0026] The degree of branching of the polyethylene resin is preferably 10 or less per 10,000 carbon atoms in the main chain, more preferably 8 or less, and even more preferably 5 or less. Here, the degree of branching is an issue for polyethylene resins having a weight average molecular weight of 1,000,000 or more.
[0027] [Method of manufacturing separator for non-aqueous electrolyte secondary battery] A known method for producing a polyolefin porous film can be used as a method for producing a separator for a non-aqueous electrolyte secondary battery, such as a method described in Japanese Patent No. 5,476,844 in which a pore-forming agent is added to a polyolefin resin, the resin is formed into a film, and then the pore-forming agent is removed.
[0028] A specific example of the production method includes the following steps. (1) 100 parts by weight of a polyolefin resin is kneaded with 120 to 240 parts by weight of a pore-forming agent (such as calcium carbonate) to obtain a mixture. (2) The mixture obtained in (1) is formed into a film. (3) The pore-forming agent is removed from the film obtained in (2). (4) The film obtained in (3) is stretched.
[0029] The thickness of the separator for non-aqueous electrolyte secondary batteries is preferably 5 to 20 μm, more preferably 7 to 15 μm, and even more preferably 9 to 15 μm. If the thickness is 5 μm or more, the functions required of the separator for non-aqueous electrolyte secondary batteries (such as a shutdown function) can be sufficiently obtained. If the thickness is 20 μm or less, a thin laminate separator for non-aqueous electrolyte secondary batteries can be obtained.
[0030] The weight per unit area of the separator for non-aqueous electrolyte secondary batteries is 4 to 20 g / m 2 is preferable, and 5 to 12 g / m 2 If the weight per unit area is within the above range, the weight energy density and volume energy density for use in a non-aqueous electrolyte secondary battery will be sufficiently high.
[0031] The shutdown temperature of the separator for a nonaqueous electrolyte secondary battery is preferably not more than 150° C., more preferably not more than 146° C., and even more preferably not more than 144° C. If the shutdown temperature is within the above range, sufficient safety against thermal runaway of the nonaqueous electrolyte secondary battery can be ensured.
[0032] The puncture strength of the separator for non-aqueous electrolyte secondary batteries is preferably 350gf / 13μm or more, more preferably 380gf / 13μm or more, when the thickness of the separator for non-aqueous electrolyte secondary batteries is 13μm. If the puncture strength is within the above range, the separator has sufficient mechanical strength against external forces applied to the non-aqueous electrolyte secondary batteries. Incidentally, when the puncture strength of a separator for non-aqueous electrolyte secondary batteries having a thickness of Xμm is Y, it can be converted to the puncture strength Y' when converted to a thickness of 13μm by the formula "Y'=Y×(13 / X)". In the case of a laminate separator for non-aqueous electrolyte secondary batteries in which a porous layer is laminated on one side of the separator for non-aqueous electrolyte secondary batteries, the thickness and puncture strength of the separator for non-aqueous electrolyte secondary batteries after the porous layer is peeled off may be X and Y, respectively, in the above formula.
[0033] The air permeability of the separator for nonaqueous electrolyte secondary batteries is preferably 50 to 350 s / 100 mL, more preferably 50 to 300 s / 100 mL, and even more preferably 100 to 250 s / 100 mL, in Gurley value. If the air permeability is within the above range, it can be said that there is sufficient ion permeability.
[0034] The porosity of the separator for non-aqueous electrolyte secondary batteries is preferably 20 to 80% by volume, more preferably 30 to 75% by volume. If the porosity is within the above range, the amount of electrolyte retained can be increased, and excessive current can be shut down at a lower temperature.
[0035] The pores in the separator for a non-aqueous electrolyte secondary battery preferably have a pore size of 0.1 μm or less, and more preferably 0.02 μm or more. If the pore size is within the above range, sufficient ion permeability can be obtained, and the intrusion of particles constituting the electrode can be more sufficiently prevented.
[0036] [2. Laminated separator for non-aqueous electrolyte secondary batteries] A laminate separator for a non-aqueous electrolyte secondary battery according to one aspect of the present invention is formed by laminating a porous layer on one or both sides of the separator for a non-aqueous electrolyte described above. In one embodiment, the porous layer contains a filler and a resin.
[0037] [Filler] Types of fillers include organic fillers and inorganic fillers.
[0038] Examples of organic fillers include styrene, vinyl ketone, acrylonitrile, methyl methacrylate, ethyl methacrylate, glycidyl methacrylate, glycidyl acrylate, methyl acrylate, and the like, alone or in copolymers of two or more kinds; fluororesins such as polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-ethylene copolymer, and polyvinylidene fluoride; melamine resin; urea resin; polyolefin; and polymethacrylate. The organic fillers may be used alone or in combination of two or more kinds. Among these organic fillers, polytetrafluoroethylene powder is preferred in terms of chemical stability.
[0039] Examples of inorganic fillers include materials made of inorganic substances such as metal oxides, metal nitrides, metal carbides, metal hydroxides, carbonates, and sulfates. Specific examples include powders of alumina, boehmite, silica, titanium dioxide, aluminum hydroxide, and calcium carbonate. The inorganic fillers may be used alone or in combination of two or more. Among these inorganic fillers, alumina powder is preferred in terms of chemical stability.
[0040] The shape of the filler may be, for example, approximately spherical, plate-like, columnar, needle-like, whisker-like, fibrous, etc., and any of these particles may be used. Approximately spherical particles are preferred because they are more likely to form uniform pores.
[0041] The filler content in the porous layer is preferably 1 to 60% by weight, more preferably 10 to 50% by weight, and further preferably 20 to 50% by weight. The filler content in the porous layer is calculated assuming that the total weight of the porous layer is 100% by weight. By setting the filler content in the above range, it is possible to suppress an increase in the weight of the porous layer and obtain a separator with good ion permeability.
[0042] The average particle size of the filler contained in the porous layer is preferably 0.01 to 2.0 μm, and more preferably 0.05 to 1.0 μm. In this specification, the "average particle size of the filler" refers to the volume-based average particle size (D50) of the filler. D50 refers to the particle size at which the cumulative distribution based on the volume is 50%. D50 can be measured, for example, using a laser diffraction particle size distribution analyzer (manufactured by Shimadzu Corporation, product name: SALD2200, etc.).
[0043] [resin] The resin contained in the porous layer has the function of bonding the components constituting the porous layer together, and bonding between the porous layer and the polyolefin porous film and / or between the porous layer and the electrode plate.
[0044] It is preferable that the resin used in the porous layer is insoluble in the electrolyte of the battery and is electrochemically stable within the range of use of the battery.
[0045] Examples of resins used in the porous layer include polyolefins; (meth)acrylate resins; fluorine-containing resins; polyamide resins; polyimide resins; polyamideimide resins; polyester resins; rubbers; resins having a melting point or glass transition temperature of 180°C or higher; water-soluble polymers; polycarbonate, polyacetal, polyether ether ketone, and the like.
[0046] Of the above-mentioned resins, (meth)acrylate resins, fluorine-containing resins, polyamide resins, polyimide resins, polyamideimide, polyester resins and water-soluble polymers are preferred.
[0047] As the polyolefin, polyethylene, polypropylene, polybutene, ethylene-propylene copolymer, and the like are preferable.
[0048] Examples of fluorine-containing resins include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer, as well as fluorine-containing rubbers having a glass transition temperature of 23° C. or lower among the above-mentioned fluorine-containing resins.
[0049] As the polyamide-based resin, aramid resins such as aromatic polyamides and wholly aromatic polyamides are preferred.
[0050] Specific examples of the aramid resin include poly(paraphenylene terephthalamide), poly(metaphenylene isophthalamide), poly(parabenzamide), poly(metabenzamide), poly(4,4'-benzanilide terephthalamide), poly(paraphenylene-4,4'-biphenylene dicarboxylic acid amide), poly(metaphenylene-4,4'-biphenylene dicarboxylic acid amide), poly(paraphenylene-2,6-naphthalene dicarboxylic acid amide), poly(metaphenylene-2,6-naphthalene dicarboxylic acid amide), poly(2-chloroparaphenylene terephthalamide), paraphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, metaphenylene terephthalamide / 2,6-dichloroparaphenylene terephthalamide copolymer, etc. Among these, poly(paraphenylene terephthalamide) is more preferable.
[0051] As the polyester-based resin, aromatic polyesters such as polyarylates and liquid crystal polyesters are preferred.
[0052] Examples of rubbers include styrene-butadiene copolymers and hydrogenated products thereof, methacrylate copolymers, acrylonitrile-acrylate copolymers, styrene-acrylate copolymers, ethylene propylene rubber, and polyvinyl acetate.
[0053] Examples of resins having a melting point or glass transition temperature of 180° C. or higher include polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, and polyetheramide.
[0054] Examples of the water-soluble polymer include polyvinyl alcohol, polyethylene glycol, cellulose ether, sodium alginate, polyacrylic acid, polyacrylamide, and polymethacrylic acid.
[0055] The resin used in the porous layer may be of one type alone or of two or more types in combination.
[0056] [Method for manufacturing laminated separator for non-aqueous electrolyte secondary battery] The porous layer can be formed by using a coating liquid in which a resin, a filler, and optionally other components are dissolved or dispersed in a solvent. Methods for forming the coating liquid include, for example, mechanical stirring, ultrasonic dispersion, high pressure dispersion, and media dispersion. For example, N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide can be used as the solvent.
[0057] An example of a method for forming the porous layer is a method in which the above-mentioned coating liquid is prepared, the coating liquid is applied to a polyolefin porous film, and the film is dried to form a porous layer.
[0058] The coating liquid can be applied to the polyolefin porous film by a known coating method such as a knife, blade, bar, gravure, or die coating method.
[0059] The method of removing the solvent (dispersion medium) is generally by drying. Examples of drying methods include natural drying, air drying, heat drying, and reduced pressure drying, but any method may be used as long as the solvent (dispersion medium) can be sufficiently removed. In addition, the solvent (dispersion medium) contained in the paint may be replaced with another solvent before drying. A specific example of a method of replacing the solvent (dispersion medium) with another solvent and then removing it is to replace it with a poor solvent with a low boiling point such as water, alcohol, or acetone, precipitate it, and then dry it.
[0060] 3. Non-aqueous electrolyte secondary battery components and non-aqueous electrolyte secondary batteries The nonaqueous electrolyte secondary battery member according to one embodiment of the present invention comprises a positive electrode, the above-mentioned laminated separator for nonaqueous electrolyte secondary batteries (or a separator for nonaqueous electrolyte secondary batteries), and a negative electrode arranged in this order. The nonaqueous electrolyte secondary battery according to one embodiment of the present invention includes the above-mentioned laminated separator for nonaqueous electrolyte secondary batteries (or a separator for nonaqueous electrolyte secondary batteries). The nonaqueous electrolyte secondary battery generally has a structure in which a negative electrode and a positive electrode face each other via the above-mentioned laminated separator for nonaqueous electrolyte secondary batteries (or a separator for nonaqueous electrolyte secondary batteries). In the nonaqueous electrolyte secondary battery, the battery element in which the structure is impregnated with an electrolyte is sealed in an exterior material. For example, the nonaqueous electrolyte secondary battery is a lithium ion secondary battery that obtains electromotive force by doping and dedoping lithium ions.
[0061] [Positive electrode] As the positive electrode, for example, a positive electrode sheet having a structure in which an active material layer containing a positive electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.
[0062] The positive electrode active material may be, for example, a material capable of doping and dedoping lithium ions, such as a lithium composite oxide containing at least one transition metal such as V, Mn, Fe, Co, or Ni.
[0063] Examples of the conductive agent include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and baked organic polymer compounds.
[0064] Examples of the binder include polyvinylidene fluoride, vinylidene fluoride copolymer, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, thermoplastic polyimide, polyethylene, and thermoplastic resin such as polypropylene, acrylic resin, and styrene butadiene rubber. The binder also functions as a thickener.
[0065] Examples of the positive electrode current collector include conductors such as Al, Ni, stainless steel, etc. Among them, Al is more preferable because it is easy to process into a thin film and is inexpensive.
[0066] Examples of methods for producing a sheet-like positive electrode include a method in which a positive electrode active material, a conductive agent, and a binder that constitute a positive electrode mixture are pressure-molded on a positive electrode current collector; a method in which a positive electrode active material, a conductive agent, and a binder are made into a paste using an appropriate organic solvent to obtain a positive electrode mixture, and then the positive electrode mixture is applied to a positive electrode current collector and dried to obtain a sheet-like positive electrode mixture, which is then pressed to be fixed to the positive electrode current collector.
[0067] [Negative electrode] As the negative electrode, for example, a negative electrode sheet having a structure in which an active material layer containing a negative electrode active material and a binder is formed on a current collector can be used. The active material layer may further contain a conductive agent.
[0068] Examples of the negative electrode active material include materials capable of doping and dedoping lithium ions, lithium metal, and lithium alloys. Examples of such materials include carbonaceous materials such as natural graphite, artificial graphite, cokes, carbon black, pyrolytic carbons, carbon fibers, and organic polymer compound sintered bodies; chalcogen compounds such as oxides and sulfides that dope and dedope lithium ions at a lower potential than the positive electrode; metals such as aluminum (Al), lead (Pb), tin (Sn), bismuth (Bi), and silicon (Si) that alloy with alkali metals; and cubic intermetallic compounds (AlSb, Mg ... 2 Si, NiSi 2 ), lithium nitride compounds (Li 3-x M x N (M: transition metal)).
[0069] Examples of the negative electrode current collector include Cu, Ni, stainless steel, etc. Among them, Cu is more preferable, particularly in lithium ion secondary batteries, because it is difficult to form an alloy with lithium and it is easy to process into a thin film.
[0070] Examples of the method for producing a sheet-shaped negative electrode include a method of pressurizing a negative electrode active material to be a negative electrode mixture on a negative electrode current collector, a method of making a negative electrode active material into a paste using an appropriate organic solvent to obtain a negative electrode mixture, applying the negative electrode mixture to a negative electrode current collector, drying the mixture, and pressing the sheet-shaped negative electrode mixture obtained to fix it to the negative electrode current collector, etc. The paste preferably contains the conductive agent and the binder.
[0071] [Nonaqueous electrolyte] The non-aqueous electrolyte may be, for example, a non-aqueous electrolyte obtained by dissolving a lithium salt in an organic solvent. 4 , LiPF 6 , LiAsF 6 , LiSbF 6 , LiBF 4 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 , Li 2 B 10 Cl 10 , lower aliphatic carboxylic acid lithium salts, LiAlCl 4 Among the above lithium salts, LiPF 6 , LiAsF 6 , LiSbF 6 , LiBF 4 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 and LiC(CF 3 SO 2 ) 3 At least one fluorine-containing lithium salt selected from the group consisting of:
[0072] Examples of the organic solvent include carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 4-trifluoromethyl-1,3-dioxolane-2-one, and 1,2-di(methoxycarbonyloxy)ethane; ethers such as 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropyl methyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran; esters such as methyl formate, methyl acetate, and γ-butyrolactone; nitriles such as acetonitrile and butyronitrile; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; carbamates such as 3-methyl-2-oxazolidone; sulfur-containing compounds such as sulfolane, dimethyl sulfoxide, and 1,3-propane sultone; and fluorine-containing organic solvents obtained by introducing a fluorine group into the above-mentioned organic solvents. Among the organic solvents, carbonates are more preferred, and a mixed solvent of a cyclic carbonate and an acyclic carbonate, or a mixed solvent of a cyclic carbonate and an ether is even more preferred. As a mixed solvent of a cyclic carbonate and an acyclic carbonate, a mixed solvent containing ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate is even more preferred. The mixed solvent has a wide operating temperature range, and is difficult to decompose even when a graphite material such as natural graphite or artificial graphite is used as the negative electrode active material.
[0073] [Members for non-aqueous electrolyte secondary batteries and methods for producing non-aqueous electrolyte secondary batteries] Examples of methods for producing a nonaqueous electrolyte secondary battery member include a method in which a positive electrode, the above-mentioned nonaqueous electrolyte secondary battery laminate separator (or nonaqueous electrolyte secondary battery separator), and a negative electrode are arranged in this order.
[0074] In addition, the method for producing a nonaqueous electrolyte secondary battery may be, for example, the following method. First, a nonaqueous electrolyte secondary battery member is placed in a container that will become the housing of the nonaqueous electrolyte secondary battery. Next, the container is filled with a nonaqueous electrolyte, and then the container is sealed while reducing the pressure. In this way, a nonaqueous electrolyte secondary battery can be produced.
[0075] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0077] [Measurement method] (1) Maximum heat generation, heat of fusion, melting point A differential scanning calorimeter (product name EXSTAR DSC 7020; manufactured by SII Nano Technology Co., Ltd.) was used to obtain a DSC curve of the composition made of polyolefin resin before film formation (the specific steps of the differential scanning calorimetric analysis are as follows). Since the change in the DSC curve due to film formation is negligibly small, the DSC curve obtained by this measurement can be regarded as the DSC curve of the separator for non-aqueous electrolyte secondary batteries after film formation. Step 1: Heat from 30℃ to 180℃ (10℃ / min) Step 2: Hold at 180℃ (5 minutes) Step 3: Decrease temperature from 180℃ to 128℃ (10℃ / min) Step 4: Hold at 128°C (480 minutes) Step 5: Decrease temperature from 128℃ to 30℃ (10℃ / min) Step 6: Hold at 30°C (3 minutes) Step 7: Increase temperature from 30°C to 180°C (10°C / min).
[0078] In the DSC curve obtained in step 4, the height of the maximum peak of heat generation accompanying crystallization was taken as the "maximum heat generation amount (mw / g)". In the DSC curve obtained in step 7, the area enclosed by the peak accompanying melting and the baseline was taken as the "heat of fusion (J / g)". In the DSC curve obtained in step 7, the temperature at which the maximum peak of endothermic heat accompanying melting appeared was taken as the "melting point (°C)".
[0079] (2) Film thickness The film thickness (μm) of the separator for the non-aqueous electrolyte secondary battery was measured using a high-precision digital length measuring machine manufactured by Mitutoyo Corporation.
[0080] (3) Metsuke A sample of 8 cm x 8 cm was cut out from the separator for the non-aqueous electrolyte secondary battery, and the weight W (g) of this sample was measured. Next, the basis weight (g / m2) of the separator for the non-aqueous electrolyte secondary battery was calculated based on the following formula: 2 ) was calculated. Weight=W / (0.08×0.08).
[0081] (4) Shutdown temperature A sample with a diameter of 19.4 mm was cut out from the separator for a non-aqueous electrolyte secondary battery. This sample was assembled with a 2032-type coin cell component (manufactured by Hosen Co., Ltd.). First, each component was stacked from top to bottom in the following order to form the following structure. Next, the components were sealed with a coin cell crimping tool (manufactured by Hosen Co., Ltd.) to prepare a coin cell for measurement. ·Top lid Aluminum ring (outer diameter 16mm, inner diameter 10mm, thickness 1.6mm) Spacer (Circular spacer with a diameter of 15.5 mm and a thickness of 0.5 mm) Kapton ring (outer diameter 16.4mm, inner diameter 8mm, thickness 0.05mm) ·gasket ·sample ·Lower lid.
[0082] At this time, the sample was impregnated with 10 μL of an electrolyte solution. The electrolyte solution was a mixture of propylene carbonate:NIKKOLBT-12 (manufactured by Nikko Chemicals Co., Ltd.) = 91.5:8.5 (volume ratio) and LiBF 4 The electrolyte used was LiBF 4 (Concentration: 1.0 mol / L) The temperature of the electrolyte when the coin cell for measurement was prepared was 25°C.
[0083] The temperature inside the prepared measuring coin cell was raised from room temperature to 150°C (15°C / min). At this time, the temperature inside the measuring coin cell was continuously measured with a digital multimeter (7352A; manufactured by ADC Corporation). In addition, the resistance value of the measuring coin cell at 1 kHz was continuously measured with an LCR meter (IM3523; manufactured by Hioki E.E. Corporation).
[0084] The relationship between the internal temperature of the coin cell and the resistance value of the coin cell at 1 kHz was graphed, and the intersection point of the tangent line at the point where the resistance value reached 2000 Ω and the baseline before the resistance significantly increased was determined as the shutdown temperature of the separator for non-aqueous electrolyte secondary batteries.
[0085] (5)Piercing strength A puncture test was performed using a Kato Tech KES-G5 handy compression tester under the conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 3.3 mm / sec, and the maximum puncture load (N) was taken as the puncture strength of the separator for non-aqueous electrolyte secondary batteries. The sample was clamped and fixed in a metal frame (sample holder) with a hole of 11.3 mm in diameter together with a silicone rubber packing.
[0086] (6) Air permeability A 60 mm×60 mm sample was cut out from the separator for a nonaqueous electrolyte secondary battery, and the sample was placed in the measuring section of a digital Oken air permeability tester (EGO1; manufactured by Asahi Seiko Co., Ltd.) to measure the air permeability (s / 100 mL).
[0087] (7) Molecular weight measurement The molecular weight of the polyolefin contained in the porous film was measured using a gel chromatograph Alliance GPC2000 manufactured by Waters Corp. The measurement conditions are as follows: Columns: Tosoh TSKgel GMHHR-H(S)HT 30cm x 2, TSKgel GMH6-HTL 30cm x 2 Mobile phase: o-dichlorobenzene Detector: Differential refractometer ·Flow rate: 1.0mL / min Column temperature: 140℃ ·Injection volume: 500μL.
[0088] After completely dissolving 30 mg of a sample in 20 mL of o-dichlorobenzene at 145°C, the solution was filtered through a sintered filter (pore size: 0.45 μm), and the filtrate was used for analysis. A calibration curve was prepared using 16 types of standard polystyrene with known molecular weights.
[0089] (8) Measurement of branching degree The polyolefin resin was subjected to carbon nuclear magnetic resonance (13C NMR) spectrum measurement under the following measurement conditions. Equipment: AVANCEIII 600HD manufactured by Bruker Biospin Co., Ltd. Measurement probe: 10mm cryoprobe Measurement solvent: 1,2-dichlorobenzene / 1,1,2,2-tetrachloroethane-d2 = 85 / 15 (volume ratio) mixture Sample concentration: 20mg / mL ·Measurement temperature: 135℃ Measurement method: Proton decoupling method -Number of times: 3000 Pulse width: 45 degrees Pulse repetition time: 4 seconds Measurement standard: Tetramethylsilane.
[0090] In the obtained 13C NMR spectrum, the sum of all peaks observed between 5 and 50 ppm was set to 1000. Next, the sum of the integral values of the peaks having their tops in the vicinity of 33.1 to 33.3 ppm, 38.1 to 38.3 ppm, or 39.7 to 39.9 ppm was determined as the branching degree of the polyolefin resin.
[0091] [Raw polyolefin] In this example, a separator for a non-aqueous electrolyte secondary battery was produced by mixing high molecular weight polyethylenes (polyethylenes A1 to A3) and low molecular weight polyethylenes (polyethylenes B1 to B3). The following polyethylenes A1 to A3 and B1 to B3 were used. Polyethylene A1: Mw = 5.06 million; branching degree = 0.1 / 1000C Polyethylene A2: Mw = 2.44 million; branching degree = 0.6 / 1000C Polyethylene A3: Mw = 4.79 million; branching degree = 0.4 / 1000C Polyethylene B1: Mw=2000; Melting point=127℃ Polyethylene B2: Mw=4000; Melting point=132℃ ·Polyethylene B3: Mw=1000; Melting point=107℃.
[0092] Example 1 100 parts by weight of polyethylene A1, 43 parts by weight of polyethylene B1, and 170 parts by weight of calcium carbonate (manufactured by Maruo Calcium Co., Ltd., average particle size measured by SEM = 0.07 μm) were mixed in a Henschel mixer. The mixture obtained was kneaded in a twin-screw kneader to obtain a mixture. The mixture obtained was rolled with a roller to form a film.
[0093] The obtained film was immersed in an aqueous hydrochloric acid solution (hydrochloric acid: 2-4 mol / L, nonionic surfactant: 0.1-0.5 wt%) for 6 minutes to remove calcium carbonate. Next, the film was immersed in an aqueous sodium hydroxide solution (sodium hydroxide: 0.1-2 mol / L) for 1 minute to neutralize it. Next, the film was immersed in water for 5 minutes to wash it. Next, the film was brought into contact with a drying drum heated to 50°C and dried. The dried film was taken up by a winder.
[0094] The wound film was stretched 7 times in the TD direction (stretching temperature: 100° C.). Next, the stretched film was subjected to a heat setting treatment (heat setting temperature: 130° C.). In this manner, a separator for a non-aqueous electrolyte secondary battery (1) was obtained.
[0095] Example 2 The composition of the polyolefin resin composition was changed to 100 parts by weight of polyethylene A1, 43 parts by weight of polyethylene B2, and 170 parts by weight of calcium carbonate. A separator for a non-aqueous electrolyte secondary battery (2) was obtained by the same procedure as in Example 1 except for the above.
[0096] Example 3 The composition of the polyolefin resin composition was changed to 100 parts by weight of polyethylene A2, 43 parts by weight of polyethylene B1, and 170 parts by weight of calcium carbonate. A separator for a non-aqueous electrolyte secondary battery (3) was obtained by the same procedure as in Example 1 except for the above.
[0097] Example 4 The composition of the polyolefin resin composition was changed to 100 parts by weight of polyethylene A3, 43 parts by weight of polyethylene B1, and 170 parts by weight of calcium carbonate. A separator for a non-aqueous electrolyte secondary battery (4) was obtained by the same procedure as in Example 1 except for the above.
[0098] Comparative Example 1 The composition of the polyolefin resin composition was changed to 100 parts by weight of polyethylene A3, 43 parts by weight of polyethylene B3, and 170 parts by weight of calcium carbonate. A comparative nonaqueous electrolyte secondary battery separator (1) was obtained by the same procedure as in Example 1 except for the above.
[0099] [Table 1]
[0100] 〔result〕 The measurement results of the physical properties of the nonaqueous electrolyte secondary battery separators (1) to (4) and the comparative nonaqueous electrolyte secondary battery separator (1) are shown in Table 1. As shown in Table 1, the nonaqueous electrolyte secondary battery separators (1) to (4) and the comparative nonaqueous electrolyte secondary battery separator (1) were almost the same in film thickness and basis weight. Furthermore, the nonaqueous electrolyte secondary battery separators (1) to (4) and the comparative nonaqueous electrolyte secondary battery separator (1) were almost the same in shutdown temperature of about 135° C. and air permeability of about 140 s / 100 mL.
[0101] In contrast, a large difference in puncture strength was observed between the Examples and the Comparative Examples. Specifically, the puncture strength of the nonaqueous electrolyte secondary battery separators (1) to (4) was 350 gf / 13 μm or more, while the puncture strength of the comparative nonaqueous electrolyte secondary battery separator (1) was below 350 gf / 13 μm.
[0102] In addition, the higher the maximum heat generation, the higher the puncture strength. Since the shutdown temperature and air permeability are similar throughout the Examples and Comparative Examples, it can be said that the higher the maximum heat generation, the better the balance of shutdown temperature, mechanical strength, and ion permeability of the separator for nonaqueous electrolyte secondary batteries.
[0103] Incidentally, the microporous membrane disclosed in the examples of Patent Document 1 has a thickness of 25 μm and a Gurley value of at least 605 s / 100 mL. In other words, it can be said that its ion permeability is significantly inferior to the separators for nonaqueous electrolyte secondary batteries (1) to (4). The polyethylene microporous membrane disclosed in Patent Document 2 has a thickness of 25 μm and a pin puncture strength of at most 585 gf. In other words, it can be said that its mechanical strength is significantly inferior to the separators for nonaqueous electrolyte secondary batteries (1) to (4). [Industrial Applicability]
[0104] The present invention can be used, for example, in non-aqueous electrolyte secondary batteries.
Claims
1. A separator for a non-aqueous electrolyte secondary battery made of a polyethylene resin, The maximum heat generation amount during isothermal crystallization at 128°C is 30 mW / g or more; A separator for a non-aqueous electrolyte secondary battery, further satisfying the following physical properties: Shutdown temperature: below 150°C; Puncture strength when the film thickness is 13 μm: 350 gf or more; Air permeability expressed in Gurley value: 50 to 152 s / 100 cc.
2. A separator for a non-aqueous electrolyte secondary battery made of a polyethylene resin, A separator for a non-aqueous electrolyte secondary battery, which has a maximum heat generation amount of 30 mW / g or more during isothermal crystallization at 128°C.
3. A laminate separator for a non-aqueous electrolyte secondary battery, comprising the separator for a non-aqueous electrolyte secondary battery according to claim 1 or 2, and a porous layer laminated on one or both sides of the separator for a non-aqueous electrolyte secondary battery, The porous layer contains one or more resins selected from the group consisting of (meth)acrylate-based resins, fluorine-containing resins, polyamide-based resins, polyimide-based resins, polyamideimide-based resins, polyester-based resins, and water-soluble polymers.
4. 4. The laminate separator for a non-aqueous electrolyte secondary battery according to claim 3, wherein the porous layer contains an aramid resin.
5. A positive electrode and A separator for a nonaqueous electrolyte secondary battery according to claim 1 or 2, or a laminate separator for a nonaqueous electrolyte secondary battery according to claim 3 or 4, A negative electrode; are arranged in this order.
6. A nonaqueous electrolyte secondary battery comprising the separator for a nonaqueous electrolyte secondary battery according to claim 1 or 2, the laminate separator for a nonaqueous electrolyte secondary battery according to claim 3 or 4, or the member for a nonaqueous electrolyte secondary battery according to claim 5.
Citation Information
Patent Citations
Polyethylene micro-porous film for separator, and manufacture thereof
JP1997259858A
Microporous polyolefin film and its production
JP1998298325A
Polyethylene fine porous membrane
JP1999269289A